Money Wage Cuts in Relation to Unemployment: A Rejoinder to Mr. Kaldor - Kaldor, N. (Review of Economic Studies, 1940)
Money Wage Cuts in Relation to Unemployment: A Rejoinder to Mr. Kaldor Nicholas Kaldor Nicholas Kaldor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 7, Issue 2, February 1940, Page 137, https://doi.org/10.1093/restud/7.2.137 Published: 01 February 1940